Wednesday

August 27, 2014

August 27, 2014

Posted by **Anonymous** on Monday, May 17, 2010 at 6:33pm.

(x-2)(x+9)=0

- algebra -
**Reiny**, Monday, May 17, 2010 at 6:41pmIf (A)(B) = 0 then either

A = 0 or B = 0

apply that to your equation.

- algebra -
**danny**, Wednesday, March 20, 2013 at 4:01pmz(-1)(z+3)=0

x^2 - x - 10=2

please help I really don't get it .

**Related Questions**

Algebra - Use the Zero Product Property to solve the equation: -3m(2m – 5) = 0

Algebra 1 - Use the Zero Product Property to solve the equation. 1. (x + 2)(x -...

Algebra 1 - Use the Zero Product Property to solve the equation. 1. (x + 2)(x -...

Algebra - Use the zero product property to solve the equation: -3n(2n-5)=0

Algebra 1 (Reiny) - Use the Zero Product Property to solve the following ...

algebra - use factoring and the zero-product property to solve 4a^2-11a+6=0 9r^2...

algebra - Use factoring and the zero-product property to solve the following ...

algebra - Use factoring and the zero-product property to solve the following ...

Algebra - I was asked to use factoring and the zero-product property to solve ...

Algebra - Use factoring and the zero-product property to solve the following ...